Determinant Factors affecting Earnings Quality on Manufacturing Companies - Andrew , Jason; Susanto, Yulius Kurnia; Supriatna, Dicky (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The problem statement of this paper is to get empirical about factors that impact earnings quality such as the earnings persistence, institutional ownership, accrual components, leverage, liquidity, investment opportunity set, independent commissioners, and profitability. The sample in this paper is manufacturing firm listed on IDX from 2017-2021. The population, which passed the sampling criteria, is 51 firms with 255 data. The sampling used in this research is purposive that requires criteria to be examined. To analyze all the data, the research used multiple regression analysis method. From the multiple regression tests, it can be showed that independent commissioner and profitability have an affect on earnings quality. While earnings persistence, institutional ownership, accrual components leverage, liquidity and investment opportunity set shows no affect on earnings quality. If a company has a party that supervise the work of management, the firm performance is likely to align with the interests of its shareholders. Which this leads to the increasing quality of an entity’s earnings.